PENGEMBANGAN E-MODUL BERBASIS FLIPBOOK DENGAN PENDEKATAN CONTEKSTUAL TEACHING AND LEARNING DI SMK MUHAMMADIYAH PAGUYANGAN - Arifin, Ahmad; Wakhyudi, Yukhsan (Universitas Peradaban, 2024)
This research aims to produce teaching materials in the form of flipbook-based e-modules with a contextual teaching and learning approach to procedural text material. This research uses research and development (R&D) methods with Hamzah's 4-stage ADDIE development model. Data collection was carried out through observation, interviews, questionnaires and documents. Based on the results of validation tests by material experts, they obtained a score of 80 with a percentage of 88.8% included in the valid category. The assessment from media experts received a score of 80 with a percentage of 88.8%, which is in the valid category, and the assessment from language experts received a score of 55 with a percentage of 91.6%, which is included in the very valid category. Based on the results of the validation test, it shows that the e-module is valid and suitable for use. Keywords: e-module, flipbook, pembelajaran